Evaluation of Educational Requirements among Iranian Cancer Patients Undergoing Radiotherapy - Hosseini, Sareh; Anvari, Kazem; Alvandi, Fatemeh; Bazri, Fatemeh; Moghadam, shiva; Hosseini Kamal, Farnaz (Reports of Radiotherapy and Oncology, 2024)
Introduction: Cancer is the 3rd cause of death after heart disease and injuries in Iran. Radiotherapy is one of the most effective procedures in cancer therapy, but in spite of widespread usage, its nature and side effects are still unknown for many patients. The main goal of this survey was studying various educational needs among cancer patients with specific emphasis on radiation therapy and its side effects. Material and Methods: This study was a descriptive-analytical research based on information extracted from personal interviews and files in order to determinate patients’ educational needs and their relationship with different variables such as demographic characteristics and the kind of disease among those referred to radiation therapy department in Mashhad Omid Hospital during a 6 months period. Results: Our findings show that age and marital status have a statistically significant association with educational needs (P<0.01). Also patients in early stage of their disease had higher educational requirements. Most of the patients had limited or moderate information about their disease and treatment effects (88%). In addition 46% of patients mentioned the physician as their preferred source of information. Conclusion: Our findings indicate lack of training about oncologic treatment and its side effects among our cancer patients, and emphasizes the need for a structured program to alleviate this problem. It seems that the role of physicians in this field is more significant than other health care staff.